2015
DOI: 10.4066/amj.2015.2452
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of radiation dose associated with common diagnostic procedures in emergency departments: A pilot study

Abstract: Physicians reported low confidence in their knowledge of radiation awareness and indicated the need for additional education, which would assist them in communicating the risks to patients. Furthermore, such education would assist physicians in tailoring their diagnostic imaging requests so as to minimise radiation levels in patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
0
5
1
Order By: Relevance
“…Despite the fact that 63% of the subjects had received radiation protection education, such as formal lectures, tutorials, or workshops, and 37% ( n = 95) had not, 53% of the respondents were unaware of the ICRP's international recommendations. To increase the low confidence in radiation knowledge and to help in conveying the hazards to patients, further education is required [ 19 ]. Certain limitations in this study must be considered in future studies to accurately measure the awareness, attitudes, and perceptions of dental undergraduates and interns.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that 63% of the subjects had received radiation protection education, such as formal lectures, tutorials, or workshops, and 37% ( n = 95) had not, 53% of the respondents were unaware of the ICRP's international recommendations. To increase the low confidence in radiation knowledge and to help in conveying the hazards to patients, further education is required [ 19 ]. Certain limitations in this study must be considered in future studies to accurately measure the awareness, attitudes, and perceptions of dental undergraduates and interns.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the literature show that physicians have insufficient knowledge on the amount of radiation the patient is exposed to during radiological examinations [14,15,26,27] and there is a lack of awareness at undergraduate and postgraduate level [28,29]. The curriculum of undergraduate and postgraduate education should be revised to include a broader and more effective training on the subject.…”
Section: Discussionmentioning
confidence: 99%
“…An assessment of American pediatric surgeons found that 75% of all respondents underestimated the dose delivered by CT compared with a chest x-ray [37]. In addition to lack of knowledge, factors such as crowding and lack of time may cause non-questioning of the risks associated with imaging methods [14,15,26,38,39].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations